2013
DOI: 10.1177/1352458513513057
|View full text |Cite
|
Sign up to set email alerts
|

A case of neuromyelitis optica harboring both anti-aquaporin-4 antibodies and a pathogenic mitochondrial DNA mutation for Leber’s hereditary optic neuropathy

Abstract: We report the first case of definite neuromyelitis optica (NMO) with a pathogenic mitochondrial DNA (mtDNA) mutation for Leber's hereditary optic neuropathy (LHON) (G11778A point mutation). A 36-year-old Japanese woman had experienced recurrent neurological symptoms originating from involvements of the optic nerves and spinal cord. She finally lost her bilateral vision, and spastic paraparesis and sensory disturbances below the T6 level remained despite intensive immunotherapies. Brain and spinal magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Our patient's episode of extensive spinal cord pathology could represent a separate coincidental issue, however; the coexistence of two relatively rare disorders seems particularly unlikely, given that numerous cases of apparent demyelination have been reported in LHON (Pfeffer et al 2013;Shiraishi et al 2014;Harding et al 1992;Parry-Jones et al 2008;Perez et al 2009). This syndrome, known as LHON-multiple sclerosis (LHON-MS), is essentially clini-cally and radiologically indistinguishable from multiple sclerosis, but with less ocular pain and a poorer visual prognosis (Pfeffer et al 2013;Matthews et al 2015).…”
Section: Discussionmentioning
confidence: 79%
“…Our patient's episode of extensive spinal cord pathology could represent a separate coincidental issue, however; the coexistence of two relatively rare disorders seems particularly unlikely, given that numerous cases of apparent demyelination have been reported in LHON (Pfeffer et al 2013;Shiraishi et al 2014;Harding et al 1992;Parry-Jones et al 2008;Perez et al 2009). This syndrome, known as LHON-multiple sclerosis (LHON-MS), is essentially clini-cally and radiologically indistinguishable from multiple sclerosis, but with less ocular pain and a poorer visual prognosis (Pfeffer et al 2013;Matthews et al 2015).…”
Section: Discussionmentioning
confidence: 79%
“…After decades of debate, clinicopathological studies have revealed striking differences between NMO and prototypic MS firmly establishing the two of them as distinct disease entities [23, 95, 113]. It is, therefore, interesting that in addition to Harding disease, patients with LHON have been described who developed a prominent spinal cord syndrome mimicking the radiological and pathological features of NMO [91, 122]. Additional research is clearly needed to further explore the interplay between a pathogenic LHON mutation, mitochondrial dysfunction and concurrent white matter CNS demyelinating disease [30, 85].…”
Section: Lhon Plus Phenotypesmentioning
confidence: 99%
“…[ 41 ] In a patient with LHON spinal cord lesions due to concomitant neuromyelitis optica (NMO) have been reported. [ 42 ] In patients with LHON and features of multiple sclerosis (MS), respectively NMO, it is conceivable that “demyelinating” lesions are in fact stroke-like lesions attributable to the MID with some clinical and instrumental features suggesting MS, respectively, NMO. In a patient with LHON and MS, new “inflammatory lesions” were seen on MRI of the brain and spinal cord 14 months after discontinuation of natalizumab.…”
Section: R Esultsmentioning
confidence: 99%